2010
DOI: 10.1212/wnl.0b013e3181ca9cff
|View full text |Cite
|
Sign up to set email alerts
|

A score to predict early risk of recurrence after ischemic stroke

Abstract: Background: There is currently no instrument to stratify patients presenting with ischemic stroke

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 39 publications
(59 reference statements)
2
128
3
1
Order By: Relevance
“…Similarly, we did not distinguish some other factors that may have yielded further prognostic information such as vascular territory, region (cortical vs subcortical), age, or multiplicity of infarcts. 35 Studies of the prognostic yield of plain CT scanning after TIA have yielded conflicting results. However, studies have tended to recruit subjects in the subacute phase, reported longer-term vascular outcomes and survival, and analyzed other imaging abnormalities such as leukoaraiosis in addition to infarction.…”
Section: Figure Pooled Analysis Of Association Between Abcd2 Score Anmentioning
confidence: 99%
“…Similarly, we did not distinguish some other factors that may have yielded further prognostic information such as vascular territory, region (cortical vs subcortical), age, or multiplicity of infarcts. 35 Studies of the prognostic yield of plain CT scanning after TIA have yielded conflicting results. However, studies have tended to recruit subjects in the subacute phase, reported longer-term vascular outcomes and survival, and analyzed other imaging abnormalities such as leukoaraiosis in addition to infarction.…”
Section: Figure Pooled Analysis Of Association Between Abcd2 Score Anmentioning
confidence: 99%
“…This difference could be explained by possible different frequencies of tested polymorphisms in general population. Patients with embolic stroke, particularly cardioembolic stroke caused by atrial fibrillation as was the case in 77% of our respondents, have a 5-7% risk for embolic stroke recurrences within 7-12 days after the initial stroke, with immediate risk for intracerebral hemorrhage as the result of damage related to the nature of the disease (20,21). For this vulnerable group of patients (who are under-or over anticoagulated), it is crucial to achieve anticoagulant effect and stable therapeutic dose as soon as possible, while pharmacogenetic testing seems valuable and promising.…”
Section: Discussionmentioning
confidence: 63%
“…These patients are at a 5-7% risk of embolic stroke recurrence within the first week. At the same time they have an increased risk of bleeding into the infarct zone due to the nature of the ischemic brain damage or to thrombolytic therapy side effects, with subsequent deterioration of neurological deficits (19)(20)(21)(22)(23). Therefore, those patients are also at increased risk of warfarin dosage side effects, notably of warfarin-induced brain hemorrhage and it is essential for them to have their initial doses selected on the basis of individual genotype to prevent the additional risk of dosage related complications.…”
Section: Introductionmentioning
confidence: 99%
“…Back propagation is by far the most popular neural network training algorithm that has been used to perform learning for multilayer feed-forward neural networks (Russell and Norving, 1995). Ay et al (2010) there is currently no instrument to stratify patients presenting with ischemic stroke according to early risk of recurrent stroke. However, in the Communications and Public Liaison, (2008) the symptoms of stroke are distinct because they happen quickly, for instance Sudden numbness or weakness of the face, arm, or leg (especially on one side of the body), Sudden confusion, trouble speaking or understanding speech, Sudden trouble seeing in one or both eyes, Sudden trouble walking, dizziness, loss of balance or coordination and Sudden severe headache with no known cause.…”
Section: Resultsmentioning
confidence: 99%